2022
DOI: 10.1371/journal.pone.0267881
|View full text |Cite|
|
Sign up to set email alerts
|

Microbiomes and Planctomycete diversity in large-scale aquaria habitats

Abstract: In commercial large-scale aquaria, controlling levels of nitrogenous compounds is essential for macrofauna health. Naturally occurring bacteria are capable of transforming toxic nitrogen species into their more benign counterparts and play important roles in maintaining aquaria health. Nitrification, the microbially-mediated transformation of ammonium and nitrite to nitrate, is a common and encouraged process for management of both commercial and home aquaria. A potentially competing microbial process that tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The results of this study showed that the decrease in the relative abundance of Proteobacteria and Bacteroidetes and the increase in the relative abundance of Acidobacteria in PBCA and PBCF resulted from the supplementation of C. pyrenoidosa to the PBC system. Planctomycetota can transform TAN and NO − 2 ─N to nitrogen under low DO conditions through the anammox pathway [34]. Compared with IBF, the relative abundance of Planctomycetota increased with increasing bacterial community diversity in biofilms.…”
Section: Discussionmentioning
confidence: 98%
“…The results of this study showed that the decrease in the relative abundance of Proteobacteria and Bacteroidetes and the increase in the relative abundance of Acidobacteria in PBCA and PBCF resulted from the supplementation of C. pyrenoidosa to the PBC system. Planctomycetota can transform TAN and NO − 2 ─N to nitrogen under low DO conditions through the anammox pathway [34]. Compared with IBF, the relative abundance of Planctomycetota increased with increasing bacterial community diversity in biofilms.…”
Section: Discussionmentioning
confidence: 98%